Role of social media uses and social comparison on self-esteem - Shabrina Dirmayanti; Setiasih Setiasih (University of Merdeka Malang, 2024)
ABSTRACTThis study aims to explain the role of social media use and social comparison on self-esteem. The participants used in this study were 105 people who actively have social media and an age range of 18-34 years who were collected through purposive sampling technique. The instrument used in this research is The Instagram Intensity Scale, adapted from a study conducted by Ellison, Steineld, & Lampe (2007), The Questionnaire of the Iowa-Netherlands Comparison Orientation Measure proposed by Gibbons and Buunk (1999), and Rosenberg Self Esteem Scale (RSES). This study uses a linear correlation test (one tailed) which finds a correlation between variables using social media and social comparisons on self-esteem, but the correlation is low (.123).ABSTRACTPenelitian ini bertujuan untuk menjelaskan peran social media uses dan social comparison terhadap self-esteem. Partisipan yang dipakai dalam penelitian ini adalah 105 orang yang aktif memiliki media sosial dan rentang usia 18-34 tahun yang dikumpulkan melalui teknik purposive sampling. Instrumen yang dipakai dalam penelitian ini adalah The Instagram Intensity Scale, diadaptasi dari studi yang dilakukan oleh Ellison, Steinfeld, & Lampe (2007), The Questionnaire of the Iowa-Netherlands Comparison Orientation Measure Proposed by Gibbons and Buunk (1999), dan Rosenberg Self Esteem Scale (RSES). Penelitian ini menggunakan uji korelasi linear (one tailed) yang mendapatkan adanya korelasi antar variabel social media uses dan social comparison terhadap self-esteem, namun korelasinya rendah (.123)